1994
DOI: 10.1152/ajpendo.1994.266.1.e57
|View full text |Cite
|
Sign up to set email alerts
|

Physiological role of galanin in the regulation of anterior pituitary function in humans

Abstract: The aim of our study was to elucidate the physiological role of the neuropeptide galanin in the regulation of anterior pituitary function in human subjects. Six healthy men (age range 26-35 yr, body mass index range 20-24 kg/m2) underwent in random order 1) an intravenous bolus injection of growth hormone-releasing hormone (GHRH)-(1-29)-NH2 (100 micrograms) + thyrotropin-releasing hormone (TRH, 200 micrograms) + luteinizing hormone-releasing hormone (LHRH, 100 micrograms) + corticotropin-releasing hormone (CRH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…The evidence that GAL exerts a role in modulating the pituitary function has been obtained when two G-protein-coupled receptors Gal-R2 and Gal-R3 have been observed in pituitary tissue [48, 49, 50]. Furthermore, a direct effect of GAL on GH secretion in calf [33], rat [51]and humans [52]has been reported. Even if the mechanism of action has not been elucidated yet, it has been suggested that GAL may act together with GHRH, since the GAL gene is coexpressed with the GHRH gene [53].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence that GAL exerts a role in modulating the pituitary function has been obtained when two G-protein-coupled receptors Gal-R2 and Gal-R3 have been observed in pituitary tissue [48, 49, 50]. Furthermore, a direct effect of GAL on GH secretion in calf [33], rat [51]and humans [52]has been reported. Even if the mechanism of action has not been elucidated yet, it has been suggested that GAL may act together with GHRH, since the GAL gene is coexpressed with the GHRH gene [53].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, galanin intravenous (i.v.) administration was found to slightly lower basal ACTH plasma concentration in healthy human volunteers and to blunt ACTH response to CRH (111). However, in the rat the acute subcutaneous (s.c.) galanin injection was shown to evoke a significant rise in the blood level of ACTH (107,112), although the prolonged galanin administration (for up to 4 days) is ineffective (112).…”
Section: Effects Of Galanin On the Hpa Axismentioning
confidence: 91%
“…To summarize, galanin is colocalized with CRH in the paraventricular-nucleus neurons, and with ACTH in pituitary corticotrophs (3)(4)(5)(6)(7). Galanin administration slightly lowers basal ACTH plasma concentration and blunts ACTH response to CRH in healthy human volunteers (8) and inhibits ACTH release in vitro from rat corticotrophs (6), but enhances ACTH and glucocorticoid blood levels in both normal and ether-stressed rats (9).…”
Section: Introductionmentioning
confidence: 98%